BIAS-BIAS KULTURAL DALAM WARNA PUTIH IDEAL - Burhanudin Ahmad Yani, Eny Kustiyah (PROSIDING, 2014)
This research aims at revealing cultural biases in the whitening cream advertisements on television. The method of the research is descriptive qualitative. The primary sources of data are four whitening cream advertisements which consist of Shireen Sungkarâs Fair and Lovely, Laudya Cyntia Bellaâs Garnier Light Complete, Agnes Monicaâs Olay Natural White, and Paramitha Rusadiâs Magic Plus White Cream. The present researcher employs library research and note-taking technique to collect the data. Whereas the type of data are words, phrases, clauses, sentences and narration. Postcolonial theory used to analize the data in this research. The present researcher employs semiotics approach for deeper understanding. The outcome of the research is that there are cultural biases in the formulation of white as beauty ideal which turn into racialized beauty.Key words: cultural biases, white skin